2016
DOI: 10.1097/fjc.0000000000000379
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic Acid Inhibits Oxidation of ApoB-containing Lipoprotein Particles of Different Size In Vitro When Administered Alone or in Combination With Atorvastatin Active Metabolite Compared With Other Triglyceride-lowering Agents

Abstract: Abstract:Eicosapentaenoic acid (EPA) is a triglyceride-lowering agent that reduces circulating levels of the apolipoprotein B (apoB)-containing lipoprotein particles small dense low-density lipoprotein (sdLDL), very–low-density lipoprotein (VLDL), and oxidized low-density lipoprotein (LDL). These benefits may result from the direct antioxidant effects of EPA. To investigate this potential mechanism, these particles were isolated from human plasma, preincubated with EPA in the absence or presence of atorvastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 62 publications
0
50
0
2
Order By: Relevance
“…Despite the high unsaturation of fish oil fatty acids however it showed antioxidant effect in the present study which agreed with the previous works 48,49 . EPA was reported as potent antioxidant due to its distinct lipophilic and electron stabilization property 50,51 . EPA also improves HDL function represented by enhancing cholesterol efflux, anti-inflammatory and antioxidant effect 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high unsaturation of fish oil fatty acids however it showed antioxidant effect in the present study which agreed with the previous works 48,49 . EPA was reported as potent antioxidant due to its distinct lipophilic and electron stabilization property 50,51 . EPA also improves HDL function represented by enhancing cholesterol efflux, anti-inflammatory and antioxidant effect 52 .…”
Section: Discussionmentioning
confidence: 99%
“… 30 More recently, Mason et al showed that in vitro eicosapentaenoic acid (EPA), a triglyceride-lowering agent, inhibited LDL oxidation, and the addition of AV at low concentrations enhanced this inhibition. 31 …”
Section: Discussionmentioning
confidence: 99%
“…These pleiotropic effects of EPA are not all shared by DHA [79], and therefore EPA may be unique among omega-3 PUFAs regarding potential benefit to patients on hemodialysis. In a notable randomized, multicenter, double-blind, controlled study ( n = 206) by Svensson et al [25], treatment of chronic hemodialysis patients with purified EPA+DHA did not lead to a significant reduction in CV events and death, but did result in a significant reduction in the number of secondary MIs.…”
Section: Discussionmentioning
confidence: 99%